The concise Oxford dictionary of linguistics - Matthews, P. H. (Peter Hugoe); Oxford University Press (Oxford : New York : Oxford University Press, 2007)
With over 3,150 entries, this fully revised and updated work, is the most authoritative dictionary of linguistics of its kind available. The dictionary covers every aspect of this multidisciplinary field, including sociolinguistics, language theory and history, language families, and major languages from all over the world (including major national/regional dialects), phonetics, formal semantics, and key figures and ideas in linguistics. With over 150 new entries, this second edition now boasts greatly enhanced coverage of sociolinguistics, new entries on notable recent theorists in the field, and expanded coverage of regional dialects. Wide-ranging and accessible, this dictionary is an ideal reference and a great introduction to linguistics for the general reader with an interest in the theory and structure of language.
Mode of access: World Wide Web via Oxford reference online.
Electronic reproduction.
Keywords: Linguistics -- Dictionaries; Linguistique -- Dictionnaires -- Sources d'information électroniques.